Insights on prospects of nano-siRNA based approaches in treatment of Cancer - Goyal, Rajat; Chopra, Hitesh; singh, Inderbir; Dua, Kamal; Gautam, Rupesh K. (Frontiers in Pharmacology, 2022)
siRNA interference, commonly referred to as gene silence, is a biological mechanism that inhibits gene expression in disorders such as cancer. It may enhance the precision, efficacy, and stability of medicines, especially genetic therapies. However, obstacles such as the delivery of oligonucleotide drugs to inaccessible areas of the body and the prevalence of severe side effects must be overcome. To maximize their potential, it is thus essential to optimize their distribution to target locations and limit their toxicity to healthy cells. The action of siRNA may be harnessed to delete a similar segment of mRNA that encodes a protein that causes sickness. The absence of an efficient delivery mechanism that shields siRNA from nuclease degradation, delivers it to cancer cells and releases it into the cytoplasm of specific cancer cells without causing side effects is currently the greatest obstacle to the practical implementation of siRNA therapy. This article focuses on combinations of siRNA with chemotherapeutic drug delivery systems for the treatment of cancer and gives an overview of several nanocarrier formulations in both research and clinical applications.